Predicting Non-response to Ranibizumab in Patients with Neovascular Age-related Macular Degeneration. (December 2014) - van Asten, Freekje; Rovers, Maroeska M.; Lechanteur, Yara T. E.; Smailhodzic, Dzenita; Muether, Philipp S.; Chen, John; den Hollander, Anneke I.; Fauser, Sascha; Hoyng, Carel B.; van der Wilt, Gert Jan; Klevering, B. Jeroen
Abstract Purpose: To validate known and determine new predictors of non-response to ranibizumab in patients with neovascular age-related macular degeneration (AMD) and to incorporate these factors into a prediction rule. Methods: This multicenter, observational cohort study included 391 patients treated with ranibizumab for neovascular AMD. We performed genetic analysis for single nucleotide polymorphisms in AMD-associated genes and collected questionnaires regarding environmental factors and disease history. The primary outcome was non-response to treatment, defined as a loss of visual acuity ≥30% of letters. Results: Of the 391 patients, 47 were classified as non-responsive. Independent predictors for non-response were age, baseline visual acuity, diabetes mellitus and accumulation of risk alleles in the CFH, ARMS2 and VEGF-A genes. The area under the receiver operating characteristic curve was 0.77 (95% confidence interval 0.70–0.84). We derived a clinical prediction rule, with possible total risk scores ranging from 0–19 points. The absolute risk of non-response varied from 3–52% between risk score groups. Conclusion: This is an important step towards a clinical prediction rule that can aid clinicians in identifying AMD patients with increased likelihood of non-response, and consequently contribute to making shared treatment decisions.